Identifikasi Ekstrak Metanol Biji Kakao (Theobroma cacao L.) Sebagai Bahan Dasar Pasta Gigi - Nuraskin, Cut Aja; Reca; Salfiyadi, Teuku (Program Studi Kesehatan Masyarakat Universitas Sari Mutiara Indonesia, 2022)
Simplistic is a natural material used for medicine and has not undergone a process change in the form of dried material. Drying is needed in maintaining the quality of a simplistic. This study aims to analyze the amount of methanol extract of cocoa beans (Theobroma cacao L.), and calculate yield values, simplistic dry weight, drying loss, extract weight, percent yield and identify the active compounds in cocoa beans taken from the Sare Aceh area, Aceh Besar district. Aceh Province. This research begins with the wind drying method. Extraction was carried out by maceration method using methanol solvent in a ratio of 1:10 for 3x 24 hours. Then, the extract was concentrated with a rotary evaporator, the yield value was calculated and the phytochemical test was carried out. The identification results showed a simplistic dry weight of 1,300 grams, drying loss 2.448 grams, yield of 4.75%, extract weight of 61.78 grams. The results of phytochemical screening of samples of cocoa bean methanol extract contained phenolic compounds, flavonoids, tannins, terpenoids, saponins and alkaloids. Conclusion The methanol extract of Sare Aceh cocoa beans contains secondary metabolic content with a yield of 4.75. Suggestion It is recommended that the methanol extract of cocoa beans be suitable as an ingredient as a basic ingredient of medicine.